Gyrocheilos W. T. Wang (Gesneriaceae) a new genus for the flora of Vietnam - Phuong, Vu Xuan (Academia Journal of Biology, 2014)
Gyrocheilos W. T. Wang (Gesneriaceae) a new genus for the flora of Vietnam